A multibeam slot antenna using dual-layer metasurface. Issue 6 (18th August 2021) - Fan, Tingting; Chen, Xinwei; Han, Guorui; Han, Liping; Liu, Yufeng; Zhang, Wenmei
ABSTRACT: A novel multibeam slot antenna using metasurface is presented in this communication. This antenna is fed by a coupling aperture and its radiating element consists of dual-layer metasurfaces formed by different units. By employing the rectangular loop slot as the coupling aperture, a wide impedance bandwidth is obtained. Meantime, a dual-layer cross-placed checkerboard metasurface is utilized to generate four beams and expand the operation bandwidth. The experimental results demonstrate that the antenna has a bandwidth of 1.37 GHz (2.18–3.55 GHz). Moreover, the four beams point at ( φ, θ ) = (180°, 23°), (270°, 23°), (0°, 23°), and (90°, 23°) and the maximum gain reaches 7.63 dBi.